(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the dynamic landscape of the Indian Information Technology (IT) industry, characterized by rapid technological advancements and intense global competition, the retention of a skilled workforce is imperative for organizational success. This research paper delves into the intricate relationship between work-life balance practices and employee retention in the context of the Indian IT sector. Utilizing a convenient sampling method and a robust sample size of 518 professionals, this study employs advanced statistical tools, including regression analysis, to comprehensively examine the impact of work-life balance initiatives on retaining talent.